Becoming : basic considerations for a psychology of personality - Allport, Gordon W. (Gordon Willard), 1897-1967 (USA : Yale University Press, 1955)
Modern psychology is in a dilemma, Allport states, for it has trimmed down the image of man as a free democratic being. He appraises the present state of the psychology of personality and indicates its relevance to human welfare and religion. This volume is based on the Terry Lectures, which the author delivered at Yale University in 1954
The case for and against psychology -- The Lockean tradition -- The Leibnitzian tradition -- The goal of psychology -- The dilemma of uniqueness -- Disposition -- Unsocial beginnings -- The importance of early affiliation -- Tribalism and individualism -- Is the concept of self necessary? -- The proprium -- The fusion of propriate functions -- Critique -- Chance, opportunistic, and oriented becoming -- Motivation and tension -- Conscience -- Schemata of value -- Anxiety and culture -- Freedom -- Structure of personality -- The religious sentiment -- Epilogue : psychology and democracy
Includes bibliographical references and index
Keywords: Psychology; Personality; Personality development; Personality; Personality Development; Psychology